Hysteroscopy in evaluation of intrauterine causes of abnormal uterine bleeding - Gandotra, Nikita; Sunil, Isha; Zargar, Shazia (International Journal of Research in Medical Sciences, 2020)
Background: Various endometrial pathologies contribute to a large proportion of cases of abnormal uterine bleeding (AUB) during the reproductive years as well as after menopause. Methods: This is a retrospective observational study conducted in department of Obstetrics and Gynaecology at SMGS Hospital, Jammu. 200 patients between 20-70 years age presenting to gynaecology OPD with abnormal uterine bleeding between January 2019 to December 2019 were studied. All patients were subjected to thorough clinical evaluation followed by hysteroscopy. Data collected from medical records, analysed and various intrauterine causes of AUB were studied. Hysteroscopy directed biopsies were taken in the same sitting and sent for histopathology and culture. Results: Mean age of patients in our study was 45 years with majority of patients in 40-50-year age group (69%). Most common symptom reported was menorrhagia (48%) followed by menometrorrhagia (18%) and polymenorrhea (10%). Hysteroscopy detected intrauterine abnormality in 59% cases. Most common being hyperplastic endometrium in 52 patients (26%) followed by polyp (20%). 14 (7%) had sub mucous fibroid, 8 (4%) had atrophic endometrium and 2 (1%) had intrauterine adhesions. Conclusion: Hysteroscopy provides a simple & easy method for visualization of the cervical canal & uterine cavity for the evaluation of AUB. Hysteroscopic pattern recognition is a useful concept to triage women who require sampling for histopathological diagnosis.